Shipboard and ground measurements of atmospheric particulate mercury and total mercury in precipitation over the Yellow Sea region - Duc Luong Nguyen; Kim, Jin Young; Shim, Shang-Gyoo; Ghim, Young Sung; Zhang, Xiao-Shan (ELSEVIER SCI LTD, 2016)
The first ever shipboard measurements for atmospheric particulate mercury (Hg(p)) over the Yellow Sea and ground measurements for atmospheric Hg(p) and total mercury (THg) in precipitation at the remote sites (Deokjeok and Chengshantou) and the urban sites (Seoul and Ningbo) surrounding the Yellow Sea were carried out during 2007-2008. The Hg(p) regional background concentration of 56.3 +/- 55.6 pg m(-3) over the Yellow Sea region is much higher than the typical background concentrations of Hg(p) in terrestrial environments (<25 pg m(-3)) which implies significant impact of anthropogenic mercury emission sources from East Asia. The episodes of highly elevated Hg(p) concentrations at the Korean remote site were influenced through long-range transport from source regions in the Liaoning Province one of China's most mercury-polluted regions and in the western region of North Korea. Interestingly, wet scavenging of atmospheric Hg(p) is the predominant mechanism regulating concentration of THg in precipitation at the Chinese sites; whereas, wet scavenging of gaseous oxidized mercury (GOM) might play the more important role than that of Hg(p) at the Korean sites. The highest annual wet and dry deposition fluxes of Hg were found at the Ningbo site. The comparison between wet and dry deposition fluxes suggested that dry deposition might play the more important role than wet deposition in Chinese urban areas (source regions); whereas, wet deposition is more important in Korean areas (downwind regions). (C) 2016 Elsevier Ltd. All rights reserved.